Defying decomposition: the curious case of choline chloride - Adriaan van den Bruinhorst; Jocasta Avila; Martin Rosenthal; Ange Pellegrino; Manfred Burghammer; Margarida Costa Gomes (Nature Communications, 2023)
Abstract Chemists aim to meet modern sustainability, health, and safety requirements by replacing conventional solvents with deep eutectic solvents (DESs). Through large melting point depressions, DESs may incorporate renewable solids in task-specific liquids. Yet, DES design is complicated by complex molecular interactions and a lack of comprehensive property databases. Even measuring pure component melting properties can be challenging, due to decomposition before melting. Here we overcame the decomposition of the quintessential DES constituent, choline chloride (ChCl). We measured its enthalpy of fusion (13.8 ± 3.0 kJ ⋅ mol) and melting point (687 ± 9 K) by fast scanning calorimetry combined with micro-XRD and high-speed optical microscopy. Our thermodynamically coherent fusion properties identify ChCl as an ionic plastic crystal and demonstrate negative deviations from ideal mixing for ChCl—contradicting previous assumptions. We hypothesise that the plastic crystal nature of ammonium salts governs their resilience to melting; pure or mixed. We show that DESs based on ionic plastic crystals can profit from (1) a low enthalpy of fusion and (2) favourable mixing. Both depress the melting point and can be altered through ion selection. Ionic plastic crystal-based DESs thus offer a platform for task-specific liquids at a broad range of temperatures and compositions.